Investigación Cualitativa en Ciencias Sociales: El Caso de la Educación - Sánchez-Gómez, María Cruz; Hernández-Ramos, Juan Pablo; Costa, António Pedro (Fronteira: Journal of Social, Technological and Environmental Science, 2019)
Investigación Cualitativa en Ciencias Sociales: El Caso de la Educación